The avifaunal survey at Important Bird Areas in western Mongolia - Purevdorj, Zoljargal; Paek, Woon Kee; Munkhbayar, Munkhbaatar; Ganbold, Onolragchaa; Bing, Gi-Chang; Jargalsaikhan, Ariunbold; Purevee, Erdenetushig; Paik, In-Hwan; Choi, Won-Suk; Jargal, Namsrai; Lee, Joon Woo (The Korean Journal of Ornithology, 2019)
In 2018, the avifaunal surveys at western Mongolian Important Bird Areas (IBAs) were conducted at 23 sites in three times surveys in May, July, and September. Western Mongolian landscape is characterized by diverse natural zones that dominated by a high mountain range and, wetlands or lakes. Therefore, fresh water high mountain lakes and mountain based IBA sites are common in this region. A total of 131,607 individuals of 201 species that belong to 41 families and 17 orders were recorded in this study. Among these order, Passeriformes was accounted for a higher number of species with 78 species, followed by Charadriiformes with 42 species and Falconiformes, Anseriformes with 26 species, respectively. In addition, the majority of counted birds were (42,121) belong to Anseriformes, while Falconiformes was accounted for the fewest number of counted birds (978). Furthermore, a total of 12 Globally Threatened Birds (GTBs) were recorded including, two Endangered and 10 Vulnerable. According to our findings from this investigation, the high abundance of livestock and tourism activities at wetlands that considered as the most valuable avifaunal hotspot in western Mongolia. In addition, findings also revealed that there is still a need monitoring on actual negative impact from these threats to the bird communities at these hotspots. KCI Citation Count: 0